2006
DOI: 10.1039/b517462g
|View full text |Cite
|
Sign up to set email alerts
|

The ammonia-free partial reduction of substituted pyridinium salts

Abstract: This paper reports a study into the partial reduction of N-alkylpyridinium salts together with subsequent elaboration of the intermediates thus produced. Activation of a pyridinium salt by placing an ester group at C-2, allows the addition of two electrons to give a synthetically versatile enolate intermediate which can be trapped with a variety of electrophiles. Furthermore, the presence of a 4-methoxy substituent on the pyridine nucleus enhances the stability of the enolate reaction products, and hydrolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 52 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…After learning that aryl halides such as benzyl Iodide and 4-methoxybenzyl iodide react with disubstituted pyridines to give pyridinium salts our investigations started with formation of pyridinium salt from 4-methoxybenzyl bromide 16 rather than the iodide 11 earlier prepared by Donohoe [5,7]. Preparation of the 4-methoxybenzyl bromide 16 followed the procedure used by Donohoe.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After learning that aryl halides such as benzyl Iodide and 4-methoxybenzyl iodide react with disubstituted pyridines to give pyridinium salts our investigations started with formation of pyridinium salt from 4-methoxybenzyl bromide 16 rather than the iodide 11 earlier prepared by Donohoe [5,7]. Preparation of the 4-methoxybenzyl bromide 16 followed the procedure used by Donohoe.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, it was decide that other electron-rich benzyl rings be investigated. 3,4,5-Trimethoxybenzyl bromide 15 was therefore prepared from cheaply commercially available 3,4,5-trimethoxybenzaldehyde via the alcohol 14 before converting it to the bromide using procedure followed by Donohoe [7,[15][16][17][18]. Reduction of the benzaldehyde to the alcohol 14 was successfully achieved by use of NaBH4 in a solution of THF : H2O in a ratio of 97:3, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary results showed that Birch reduction of salts of 2-carboxyisopropyl pyridine afforded the desired reaction products in very low yields, most probably because of the instability of the resulting 1,2-dihydropyridine, an inconvenience overcome by the introduction of a methoxy group at C-4, as in compounds 107 [49]. Indeed, upon acidic hydrolysis of the reduction mixture, which is incompatible with liquid ammonia as a solvent, the expected 1,2-dihydropyridines 109 were supposed to transform into the corresponding stable dihydropyridones 110 [50].…”
Section: Ammonia-free Birch Reductionsmentioning
confidence: 99%